Monitoring reclamation settlements in coastal areas of Singapore using Sentinel-1A InSAR data - Chong, Hui Min (2018)
In this project, the aim is to learn about the methodology of interferometry and its various applications through applying a preferred interferometry processing on real satellite data. The end product of this project is an identification of permanent scatterers and their displacement rates to monitor the land reclamation areas in Singapore. Through the processing of data from the Sentinel-1 mission satellite in SNAP and exporting the files to StaMPS, the permanent scatterers will be identified and computations will be made to find out the displacement rates of the marked pixels. High displacement rates or jumps in values will indicate that the areas are experiencing large movements. Predictions will be made based on prior knowledge of Singapore’s landscape and conditions.